The dragonfly’s face of the multidimensional Dr. Angelo Barbosa Monteiro Machado: a short bio-bibliography - Pinto, Ângelo Parise (Zootaxa, 2016)
In this special issue celebrating the Brazilian researcher Dr. Angelo Barbosa Monteiro Machado’s 80th birthday, I present a very short biographical overview focused on his prolific career as odonatologist. The doctor, professor, children’s book writer, conservationist, comedian, neuroanatomist, and eventually odonatologist Professor Angelo has published more than 110 papers, of which 79 are on dragonflies. He erected 97 new names, an impressive number for a small and relatively well-known order of insects. Here are presented annotated checklists of his publications on dragonflies (from 1953 to September of 2015), and nomina, as well as few comments of his impact on Neotropical odonatology as a whole.